Separation and identification of chemicals compound obtained from selected bio oil / Airin Aezzira Kamaruzzaman - Kamaruzzaman, Airin Aezzira (2016)
Bio-oil is composed of 200 types of different organic compounds. It contains substantial amount of water. Bio-oil is difficult to use as transportation fuel. Thus bio oil can be separated into different high value and low volume compounds and low value and high volume compounds. The high value fraction can be used as chemicals and high volume fraction can be used as a fuel and the mode of this application can make bio-oil more competitive to the conventional fuel. Fractional distillation has been used in this work to separate the different groups of chemicals depending on the boiling point range. The groups of chemicals have been collected by using fractionation column with 10 plates. The rest of the liquid can be considered as tar and utilized for bio-plastic production. Each of the fractions was analyzed to determine the constituent compound by using Gas Chromatography Mass Spectrometry (GCMS) and Fourier Transform Infrared (FTIR) Spectroscopy. Compounds were considered in eleven main groups: acids, esters, linear aldehydes and ketones, cyclic ketones, furans, alcohols, sugar, phenols, other oxygenated cyclic compounds, hydrocarbons, ethers and nitrogen containing compounds. The effect of distillation temperature on physical and chemical characterization of each bio-oil fraction was investigated. The results showed that this distillation method has potential to be utilized for large scale separation of bio-oil.